A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

The Meanings and Dividends of Man the Hunter - Vivek V. Venkataraman; Edward H. Hagen; Duncan Stibbard-Hawkes; Raymond Hames; Sheina Lew-Levy; Haneul Jang; Luke Glowacki; Jordie Hoffman; Karen Kramer; Helen Elizabeth Davis; Kathrine Starkweather; Barry Hewlett; et al. (Evolution and Human Behavior, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Multisite evaluation of microtensiometer and osmotic cell stem water potential sensors in almond orchards - Isaya Kisekka; Srinivasa Rao Peddinti; Peter Savchik; Liyuan Yang; Mae Culumber; Khalid Bali; Luke Milliron; Erica Edwards; Mallika Nocco; Clarissa A. Reyes; Robert J. Mahoney; Kenneth Shackel; et al. (Computers and Electronics in Agriculture, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

Experimental constraints on barium isotope fractionation during adsorption–desorption reactions: Implications for weathering and erosion tracer applications - Alasdair C.G. Knight; Edward T. Tipper; Harold J. Bradbury; Alexandra V. Turchyn; Christoff Andermann; Heye Freymuth; Tim Elliott; Luke Bridgestock (Geochimica et Cosmochimica Acta, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The impact of adsorption–desorption reactions on the chemistry of Himalayan rivers and the quantification of silicate weathering rates - Alasdair C.G. Knight; Emily I. Stevenson; Luke Bridgestock; J. Jotautas Baronas; William J. Knapp; Basanta Raj Adhikari; Christoff Andermann; Edward T. Tipper (Earth and Planetary Science Letters, 2024)

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A Low-Cost, DIY Ultrasonic Water Level Sensor for Education, Citizen Science, and Research - Philip Bresnahan; Ellen Briggs; Benjamin Davis; Angelica Rodriguez; Luke Edwards; Cheryl Peach; Nan Renner; Harry Helling; Mark Merrifield (Oceanography, 2023)
A low-cost (~$100), do-it-yourself (DIY) ultrasonic water level sensor/datalogger has been designed, constructed, and tested for use in education, citizen/community science, and research settings. The sensor package comprises an ultrasonic distance sensor, a microcontroller running Arduino firmware, a micro-SD card for datalogging, a real-time clock for timekeeping and sleep functions, and an OLED screen for real-time display. Electronics are housed in low-cost custom containers using either upcycled plastic containers or laser-cut acrylic. Reported ultrasonic sensor accuracy is 5 cm across a range of 15–645 cm, with an estimated power budget of 76 days of operation on a rechargeable 10 amp-hr battery. The DIY sensor has been field tested alongside two commercial sensors for 18 days in Wilmington, North Carolina, including during Tropical Storm Colin, with all sensor measurements in close agreement (e.g., root mean squared error of 1.5 cm between the DIY sensor and a proven commercial unit). Potential applications, design and construction, and deployment recommendations for the sensors are described, as well as simple and inexpensive modifications to the sensor and its packaging that could further improve performance. Preliminary lesson plans written to accompany the device for high school- and undergraduate-level educational projects are available.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Improving the Accuracy of Krill Target Strength Using a Shape Catalog - Fiona Bairstow; Sven Gastauer; Luke Finley; Tom Edwards; C. Tom A. Brown; So Kawaguchi; Martin J. Cox (Frontiers in Marine Science, 2021)
Antarctic krill are subject to precautionary catch limits, based on biomass estimates, to ensure human activities do not adversely impact their important ecological role. Accurate target strength models of individual krill underpin biomass estimates. These models are scaled using measured and estimated distributions of length and orientation. However, while the length distribution of a krill swarm is accessible from net samples, there is currently limited consensus on the method for estimating krill orientation distribution. This leads to a limiting factor in biomass calculations. In this work, we consider geometric shape as a variable in target strength calculations and describe a practical method for generating a catalog of krill shapes. A catalog of shapes produces a more variable target strength response than an equivalent population of a scaled generic shape. Furthermore, using a shape catalog has the greatest impact on backscattering cross-section (linearized target strength) where the dominant scattering mechanism is mie scattering, irrespective of orientation distribution weighting. We suggest that shape distributions should be used in addition to length and orientation distributions to improve the accuracy of krill biomass estimates.

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Transcriptional characterization of Vibrio fischeri during colonization of juvenile Euprymna scolopes - Luke R. Thompson; Kiel Nikolakakis; Shu Pan; Jennifer Reed; Rob Knight; Edward G. Ruby (Environmental Microbiology, 2017)
Summary The marine bacterium Vibrio fischeri is the monospecific symbiont of the Hawaiian bobtail squid, Euprymna scolopes , and the establishment of this association involves a number of signaling pathways and transcriptional responses between both partners. We report here the first full RNA‐Seq dataset representing host‐associated V. fischeri cells from colonized juvenile E. scolopes , as well as comparative transcriptomes under both laboratory and simulated marine planktonic conditions. These data elucidate the broad transcriptional changes that these bacteria undergo during the early stages of symbiotic colonization. We report several previously undescribed and unexpected transcriptional responses within the early stages of this symbiosis, including gene expression patterns consistent with biochemical stresses inside the host, and metabolic patterns distinct from those reported in associations with adult animals. Integration of these transcriptional data with a recently developed metabolic model of V. fischeri provides us with a clearer picture of the metabolic state of symbionts within the juvenile host, including their possible carbon sources. Taken together, these results expand our understanding of the early stages of the squid–vibrio symbiosis, and more generally inform the transcriptional responses underlying the activities of marine microbes during host colonization.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Detecting impairment associated with cannabis with and without alcohol on the Standardized Field Sobriety Tests - Luke A. Downey; Rebecca King; Katherine Papafotiou; Phillip Swann; Edward Ogden; Martin Boorman; Con Stough (Psychopharmacology, 2012)

The acute effects of 3,4-methylenedioxymethamphetamine and d-methamphetamine on human cognitive functioning - Con Stough; Rebecca King; Katherine Papafotiou; Phillip Swann; Edward Ogden; Keith Wesnes; Luke A. Downey (Psychopharmacology, 2012)

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)